The vitamin B12 analog cobinamide ameliorates azide toxicity in cells, Drosophila melanogaster, and mice. - Tat, J.; Chang, S.C.; Link, C.D.; Razo-Lopez, S.; Ingerto, M.J.; Katebian, B.; Chan, A.; Kalyanaraman, H.; Pilz, R.B.; Boss, G.R. (Clinical toxicology, 2023)
The azide anion (N3-) is highly toxic. It exists most commonly as sodium azide, which is used widely and is readily available, raising the potential for occupational incidents and use as a weapon of mass destruction. Azide-poisoned patients present with vomiting, seizures, hypotension, metabolic acidosis, and coma; death can occur. No specific azide antidote exists, with treatment being solely supportive. Azide inhibits mitochondrial cytochrome c oxidase and is likely oxidized to nitric oxide in vivo. Cytochrome c oxidase inhibition depletes intracellular adenosine triphosphate and increases oxidative stress, while increased nitric oxide causes hypotension and exacerbates oxidative damage. Here, we tested whether the cobalamin (vitamin B12) analog cobinamide, a strong and versatile antioxidant that also neutralizes nitric oxide, can reverse azide toxicity in mammalian cells, Drosophila melanogaster, and mice. We found cobinamide bound azide with a moderate affinity (Ka 2.87 × 10[5] M[-1]). Yet, cobinamide improved growth, increased intracellular adenosine triphosphate, and reduced apoptosis and malondialdehyde, a marker of oxidative stress, in azide-exposed cells. Cobinamide rescued Drosophila melanogaster and mice from lethal exposure to azide and was more effective than hydroxocobalamin. Azide likely generated nitric oxide in the mice, as evidenced by increased serum nitrite and nitrate, and reduced blood pressure and peripheral body temperature in the animals; the reduced temperature was likely due to reflex vasoconstriction in response to the hypotension. Cobinamide improved recovery of both blood pressure and body temperature. We conclude cobinamide likely acted by neutralizing both oxidative stress and nitric oxide, and that it should be given further consideration as an azide antidote.